How do you see that $\sup_{x \in X} \lim_{m \to \infty} | f_n(x) - f_m(x)| \leq \lim \inf_{m \to \infty} \sup_{x \in X} |f_n(x) - f_m (x)|$?
I thought $\sup_{x \in X} \lim_{m \to \infty} | f_n(x) - f_m(x)| = \sup_{x \in X} \lim \inf_{m \to \infty} | f_n(x) - f_m(x)|$ but then I'm not sure how to justify swapping the $\sup$ and the limit...
I thought $\sup_{x \in X} \lim_{m \to \infty} | f_n(x) - f_m(x)| = \sup_{x \in X} \lim \inf_{m \to \infty} | f_n(x) - f_m(x)|$ but then I'm not sure how to justify swapping the $\sup$ and the limit...